18 The eye's mind: perspectives on visual imagery. Issue 8 (20th July 2020) - Zeman, Adam
Abstract : Prof. Zeman trained in Medicine at Oxford University Medical School, after a first degree in Philosophy and Psychology, and later in Neurology in Oxford, at The National Hospital for Neurology in Queen Square, London and Addenbrooke's Hospital, Cambridge. He moved to Edinburgh in 1996, as a Consultant and Senior Lecturer (later Reader) in the Department of Clinical Neurosciences and to the Peninsula Medical School (now University of Exeter Medical School) in September 2005 as Professor of Cognitive and Behavioural Neurology. His specialised clinical work is in cognitive and behavioural neurology, including neurological disorders of sleep. His main research interests are disorders of visual imagery and forms of amnesia occurring in epilepsy. He has an active background interest in the science and philosophy of consciousness, publishing a wide-ranging review of the field in Brain (2001; 124:1263–1289) and an accessible introduction to the subject for a general readership (Consciousness: a user's guide, Yale University Press, 2002). In 2008 he published an introduction to neurology for the general reader, A Portrait of the Brain (Yale UP), and in 2012, Epilepsy and Memory (OUP) with Narinder Kapur and Marilyn Jones-Gotman. From 2007–2010 he was Chairman of the British Neuropsychiatry Association. He launched and continues to direct its training course in neuropsychiatry. For most of us visual imagery is a conspicuous ingredient of the imaginative experience which allows us to escape from the here and now into the past, the future and the worlds conceived by science and art. But there appears to be wide inter-individual variation in the vividness of visual imagery. Although the British psychologist Galton together with the Parisian neurologist Charcot and his psychiatrist colleague Cotard - recognised that some individuals may lack wakeful imagery entirely, the existence of 'extreme imagery' has been oddly neglected since this early work. In 2015 we coined the term 'aphantasia' to describe the lack of the mind's eye, describing 21 individuals who reported a lifelong inability to visualise (Cortex, 2015;73:378–80). Since then we have heard from around 14, 000 people, most reporting lifelong aphantasia, or its converse hyperphantasia, but also less common 'acquired' imagery loss resulting from brain injury or psychological disorder. Preliminary analyses suggests association between vividness extremes, occupational preference and reported abilities in face recognition and autobiographical memory. Many people with lifelong aphantasia nevertheless dream visually. Imagery in other modalities is variably affected. Extreme imagery appears to run in families more often than would be expected by chance. I will describe the findings of our recent pilot study of neuropsychological and brain imaging signatures of extreme imagery, and place our study of a- and hyper-phantasia in the context of the Eye's Mind project, an interdisciplinary collaboration funded by the AHRC (http://medicine.exeter.ac.uk/research/neuroscience/theeyesmind/). In addition to our work on extreme imagery, we have reviewed the intellectual history of visual imagery (MacKisack et al, Frontiers in Psychology, 515:1–16. doi: 10.3389/fpsyg.2016.00515), undertaken a recent ALE meta-analysis of functional imaging studies of visualisation (Winlove et al, Cortex, 20182018; 105:4–25) and organised an exhibition of work by artists with extreme imagery vividness (Extreme Imagination: inside the mind's eye Exeter University Press, 2018.)